Commented Translation of a Portuguese-language scientific article for Libras: an evaluation turned into reflection - Vieira, Claudia Regina (The ESPecialist, 2022)
This work is the result of a study conducted in a training course of interpreters of Libras that presented as a result the commented translation of a scientific article, chosen by the student. The objective here is to discuss the text, its relevance to the study, since it seeks to clarify the process carried out in four years of course and to present the reflections made for the translation and translation of the article into the Brazilian Sign Language - Libras, commenting the techniques used to perform the translation, bringing the assumptions studied during the Libras Language Course, mainly rescuing the authors of the Translation studies, the responsibilities of the Libras Interpreter Translator. This work is an investigative process that relied on theoretical references and, above all, experimentation for the organization of strategies for translation. This reflection is necessary at this time so that we can look at the translations in Libras that are offered to the Deaf and especially to demystify the idea that knowing the signs of Libras is sufficient for a translation of text, especially academic.